Comprehensive Review on Neuro-degenerative Type 3 DM - Chandarana, Chandani V.; Roy, Salona (Current Diabetes Reviews, 2022)
According to research, Alzheimer’s disease (AD) is considered a metabolic illness caused by defective insulin signaling, insulin resistance, and low insulin levels in the brain. Type 3 diabetes has been postulated for AD because reduced insulin signaling has molecular and physiological consequences that are comparable to type I and type 2 diabetes mellitus, respectively. The similarities between type 2 diabetes and Alzheimer’s disease suggest that these clinical trials might yield therapeutic benefits. However, it is important to note that lowering your risk of Alzheimer’s dementia, whether you have diabetes or not, is still a multidimensional process involving factors like exercise, smoking, alcohol, food, and mental challenges. The current aim is to show that the relationship between T3D and AD is based on both the processing of amyloid-β (Aβ) precursor protein toxicity and the clearance of Aβ, which are the results of impaired insulin signaling. The brain’s metabolism, with its high lipid content and energy needs, places excess demands on mitochondria and appears more susceptible to oxidative damage than the rest of the body. Current data suggests that increased oxidative stress relates to amyloid-β (Aβ) pathology and the onset of AD.
Keywords: neurodegeneration